Neurometabolic therapy in the recovery period of ischemic stroke: impact on quality of life and cognitive functions - V. V. Zakharov; N. V. Vakhnina; D. O. Gromova (Неврология, нейропсихиатрия, психосоматика)
Some recovery of impaired neurological functions (a stroke recovery period) is almost always observed within the first 6–24 months after ischemic stroke (IS). The paper discusses the mechanisms responsible for this process (neurogenesis, neuroplasticity, and readaptation) and possible approaches to the drug support of cerebral reparative processes. It presents data on the rate and etiology of poststroke cognitive impairments (CI) that are one of the important factors that negatively influence the outcome of rehabilitation measures. The results obtained from a recent study of the efficacy of the neurometabolic agent citicoline in the recovery period of IS are given. The use of citicoline is shown to cause a significant regression of CI and to improve quality of life in patients who have sustained IS for the first time.